Manhaj: Pengertian dan Kepentingannya Kepada Da’wah - Haji Syed Hussin, Syed Abdurrahman (Jurnal Usuluddin, 1998)
The article discusses the meaning of the method of dakwah, its significance and application by the Prophet (p.b.u.h) in Medina and Mecca.